Hypoglycemic activity of Hemidesmus indicus R. Br. on streptozotocin-induced diabetic rats - Gayathri, Mahalingam (Medknow Publications, 2008)
OBJECTIVE: To evaluate the antidiabetic activity of an aqueous extract of the roots of Hemidesmus indicus on blood glucose, serum electrolytes, serum marker enzymes, liver microsomal P-450 enzymes, and lipid peroxidation in the liver and kidney of streptozotocin-induced diabetic rats. MATERIALS AND METHODS: Effect of H. indicus extract on blood glucose was studied with fed, fasted and glucose-loaded diabetic and nondiabetic rat models. The effect of the extract on serum electrolytes, serum levels of key glucose metabolizing enzymes, hepatic microsomal protein and hepatic cytochrome P-450-dependent mono-oxygenase enzyme systems and lipid peroxidation in the liver and kidney of diabetic rats. One way analysis of variance and Duncan's multiple range test was used for statistical analysis. RESULTS: Oral administration of H. indicus aqueous extract to fed, fasted and glucose-loaded diabetic rats decreased blood glucose level significantly at 5 h and restored serum electrolytes, glycolytic enzymes and hepatic cytochrome P-450-dependent enzyme systems by preventing the formation of liver and kidney lipid peroxides at the end of 12 weeks of the study period. CONCLUSION: From the studies, it can be concluded that the aqueous extract of the roots of H. indicus at a dosage of 500 mg/kg/day exhibits significant antidiabetic activity. It restores the concentrations of electrolytes, glucose metabolizing enzymes, hepatic microsomal protein and hepatic cytochrome P-450-dependent mono-oxygenase enzyme systems to near normal level and also corrects the related metabolic alterations in experimentally induced diabetic rats. H. indicus administration also decreased liver and kidney lipid peroxidation products. On the basis of our findings, H. indicus could be used as an antidiabetic and antioxidant agent for the prevention and treatment of diabetes mellitus.